HUBUNGAN TINGKAT KECEMASAN TERHADAP POLA MAKAN PADA REMAJA - Permata Izza Maghfira; Eppy Setiyowati; Naila Ferdia Putri; Faizatur Rokhman; Zsuryana Aprilla Mustika Sura; Cholila; Laili Ihda Isrina (Nusantara Hasana Journal, 2023)
Among adolescents. despair and anxiety are two of the most prevalent mental illnesses. Usually, anxiety disorders that occur in adolescents will have an impact on their daily life patterns, one of which is eating patterns. The research objective was to determine whether there was a relationship between anxiety levels and eating patterns in adolescents. This type of quantitative research uses survey methods and cross-sectional approaches. Purposive sampling was used for the research sample which consisted of 40 teenagers. We can infer from the findings of this study that anxiety levels are significantly correlated with and eating patterns in adolescents with the Friedman test with a value of ρ <α (0.05) obtained ρ <α (0.05), which is 0.00. The conclusion of the study is that anxiety is related to eating patterns